The impact of genotype‐by‐environment interaction on the dry matter yield and chemical composition in timothy (Phleum pratense L.) examined by using the additive main effects and multiplicative interaction model. (20th July 2021) - Bocianowski, Jan; Radkowski, Adam; Nowosad, Kamila; Radkowska, Iwona; Zieliński, Andrzej
Abstract: Timothy‐grass ( Phleum pratense L.) is one of the most valuable pasture grasses in Poland, and the productivity of its genotypes (in the case of outcrossing grass species, the term accession instead of genotype was used in this study) varies depending on environmental conditions. In this study, we aimed to examine the accession‐by‐environment interaction for seven traits in timothy accessions grown in Southern Poland using the additive main effects and multiplicative interaction model. The plant materials used in the study included a total of 11 timothy accessions—six Polish synthetic cultivars (Skald, Egida, Emma, Skala, Skaut and Karta) and five strains (POB‐TT1, POB‐TT2, POB‐TT3, POB‐T‐100 and POB‐T‐107). All these accessions were examined in field trials at three locations, Polanowice, Nieznanice and Palikije, in two growing seasons. The field trials were conducted according to a randomized complete block design with three replicates. The AMMI analyses revealed significant effects of accession and environment as well as the accession‐by‐environment interaction for all the seven analysed traits. The cultivar Skald and the strain POB‐TT3 are recommended for inclusion in future breeding programmes as they exhibit high stability and show good average values for the majority of the examined traits.